Earthen Domes as an Economical and Sustainable Alternative to the Refugees' Camps in the Northern Region of Syria - Mohammed Alfayyad (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
As a result of the years-long conflict in Syria, many Syrians have been forced to move to safer areas near the SyrianTurkish border in the north. As a result of the deteriorating economic conditions, the displaced people are forced to live in tents in camps that lack the basic needs of human beings. In addition, these camps did not protect the residents from the severe weather conditions in summer and winter. This paper proposes a sustainable economic solution by building special earthen domes that provide independence and social interactions between the residents of the camp. The solution presents different architectural models that are adapted to the needs of the displaced and provide thermal insulation and consider the economic and social aspects by relying on earth in providing the building materials. The displaced may participate in building their own houses in a way that secures decent life.